Math, asked by rajat5841, 1 year ago

factorize 2y^3+y^2-2y-1 using factor theorem

Answers

Answered by hooda3332683
2


# if this is write answer than please mark as brainliest
Attachments:

rajat5841: i wanted it as error and trial method,long division and then the factor theorem.
lekhana49: this is one more method
Answered by lekhana49
5
2y²+y²-2y-1
=y²(2y+1) -1(2y+1)
=(y²-1) (2y+1)
=(y²-1²) (2y+1)
=it is in the form of( a²-b²) =(a+b) (a-b)
=(y+1)(y-1)(2y+1)

rajat5841: this is not what i want . i wanted the three step method
Similar questions